Perlindungan Hukum Dokter Internis Terhadap Resiko Tindakan Medis Kemoterapi Oral Pada Pasien Kanker Darah - Finly Septianto; Mohammad Zamroni (Jurnal USM Law Review)
This study aimed to analyze the authority of internal medicine specialists for oral chemotherapy in blood cancer patients and the legal protection of internal medicine specialists for oral chemotherapy in blood cancer patients. Blood cancer has a significant impact on physical, psychological, and social well-being. The commonly used treatment method is chemotherapy. Chemotherapy is usually carried out in a hospital, but there is a chemotherapy method that can be done at home, namely oral chemotherapy. Oral chemotherapy does seem more efficient, but patients who are undergoing oral chemotherapy must be careful in knowing the dosage of drugs that must be consumed. Seeing the potential for large risks, it is necessary to be careful in handling which is the authority of health workers, especially doctors who specialize in internal medicine. This research is structured using normative legal research. The results of this study indicate that there are no laws and regulations that regulate in detail related to oral chemotherapy, the clinical authority of doctors who perform oral chemotherapy, and protection for doctors and patient safety. If the doctor's actions are by professional standards and standard operating procedures, and during the treatment or care process unexpected complications occur, even resulting in the patient's death, the doctor cannot be sued.